KMT2B-dependent RFK transcription activates the TNF-α/NOX2 pathway and enhances ferroptosis caused by myocardial ischemia-reperfusion. (December 2022) - Cao, Yuanyuan; Luo, Fei; Peng, Jia; Fang, Zhenfei; Liu, Qiming; Zhou, Shenghua
Abstract: Epigenetic regulation such as histone modification is implicated in the pathogenesis of myocardial ischemia/reperfusion injury (MIRI). Lysine-specific methyltransferase 2B (KMT2B) is a histone H3 lysine 4 (H3K4) methyltransferase. This study aims at exploring the role of KMT2B-mediated histone modification in MIRI. Peripheral blood samples were collected from 30 patients with acute myocardial infarction (AMI) and 30 healthy volunteers for analyses of the expression levels of KMT2B, riboflavin kinase (RFK), tumor necrosis factor (TNF)-α, and NADPH oxidase 2 (NOX2). H9C2 cardiomyocytes and Sprague-Dawley rats were utilized for developing in vitro and in vivo models. To evaluate the effects of the aforementioned molecules on cellular damage and MIRI, short hairpin RNAs or overexpression plasmids were introduced into cardiomyocytes for gene silencing or overexpression and also, they were packaged into adenovirus vectors for in vivo interventions. Immunoprecipitation assays were conducted to assess the interactions between KMT2B and RFK and among RFK, NOX2 sub-unit p22 phox, and TNF receptor 1-associated death domain protein. KMT2B, RFK, TNF-α, and NOX2 were notably upregulated in AMI patients. KMT2B knockdown resulted in considerably attenuated cell apoptosis and reduced myocardial infarct area. Additionally, the release of pro-inflammatory proteins and ferroptosis were suppressed. Furthermore, KMT2B could promote RFK gene transcription by upregulating H3 methylation levels and consequently activate the TNF-α/NOX2 axis, which was the possible mechanism underlying the role of KMT2B in MIRI. KMT2B motivates MIRI-induced cellular injury and ferroptosis by inducing RFK transcription and mediating the TNF-α/NOX2 axis. Graphical abstract: Unlabelled Image Highlights: KMT2B, RFK, TNF-α, and NOX2 are upregulated in peripheral blood of AMI patients. KMT2B knockdown attenuates MIRI in rats or cardiomyocyte injury and ferroptosis. KMT2B upregulates the H3 methylation level to promote RFK transcription. KMT2B is involved in RFK-mediated TNF-α/NOX2 axis. KMT2B mediates MIRI in rats or cardiomyocyte ferroptosis via TNF/RFK/NOX2 axis.